Genetic engineering : modern progress or future peril? - Tagliaferro, Linda (Minneapolis : Twenty-First Century Books, 2010)
Discusses current and potential uses of genetic engineering in fields such as medicine, criminal investigation, and agriculture and examines some of the ethical questions involved.
Keywords: Genetic engineering; Genetic engineering -- Moral and ethical aspects